METAEVALUATION ACCREDITATION RESULTS OF ELECTRICAL ENGINEERING EDUCATION STUDY PROGRAM FACULTY OF ENGINEERING STATE UNIVERSITY OF JAKARTA 2010 - Readysal MONANTUN; Ihsana El KHULUQO; Istaryatiningtias ISTARYATININGTIAS (Journal of Education and Leadership in Education, 2022)
The Study Program's accreditation process is very important to to maintain the continuity of education services quality and to provide assurance that the accredited Study Program has met the quality standards set by BAN-PT. This study aims to determine the percentage level of achievement in the meta-evaluation process, the higher percentage level achievement of the meta-evaluation results means that this research instrument can be used to measure the primary evaluation with a high level of achievement. This research is a evaluation research using metaevaluation approach, the subject in this study is the primary evaluation in the form of the accreditation results of Electrical Engineering Education Study Program, Faculty of Engineering, State University of Jakarta in 2010. The research instrument is a development of the BAN-PT accreditation assessment instrument which is guided by Book VI Assessment Matrix Instrument of Undergraduate Study Program Accreditation. Data and information collection’s method by observations, documentations, group discussions and interviews. The results showed that the percentage of achievement level given by meta-evaluation calculation in average of 10 respondents was 84.59%. It can be concluded that the meta-evaluation instrument in this research can measure primary evaluations with a high percentage of achievement.